PENGARUH LAYANAN INFORMASI TENTANG WAWASAN KARIR TERHADAP SELF EFFICACY KARIR SISWA KELAS X SMK NEGERI 4 PEKANBARU - Sari, Ria Ratna Sari Ratna; Yakub, Elni Yakub; Asyari, Abu Asyari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to 1) To know the description of students' career self-efficacy before being given an insight into careers information services. 2) To know the process of providing information services on the insight of career to career self-efficacy. 3) To know the description of career self-efficacy after the given service insightful information about a career. 4) To determine differences in students' career self-efficacy before and after services insightful information about a career. 5) To determine the influence of information services on career insight to the students' career self-efficacy. Data collection tools in the form of career self-efficacy scale. The subjects were students of class X SMK 4 Pekanbaru, amounting to 213 people. Determination of the sample by using simple random sampling and sample in this study were 107 people. Overview of career self-efficacy before being given the information services that are in the category of being at 87,85%, higher categories by 6,54% and amounted to 5,61% lower categories. Overview of career self-efficacy after being given information service is at a high of 75,71% category, the category is very high at 14,95% and amounted to 9,34% medium category. Based on the results of the calculation of the correlation coefficient between and amounted to 0,61 and determinant coefficient = 0,37 this means that the contribution of information services to the career self-efficacy by 37%. It can be seen greater than (22 > 1,960) so that Ha is accepted. Means that there is an influence on self-efficacy information services career class X SMK 4 Pekanbaru TA. 2014/2015. Keywords: information services, self efficacy